Pattern of transcatheter interventional procedure have done in Cath lab and their immediate outcome: one year experience at Bangladesh Shishu hospital and institute - Munsi, M. Abu Sayed; Akther, Maher; Khan, M. Khalid Ebna Shahid; Saha, Chandan (International Journal of Contemporary Pediatrics, 2023)
Background: Congenital heart disease (CHD) is defined by structural and functional malformations of the heart. If CHD not managed through appropriate interventions, it affects quality of life of the individual and potential premature death. Objectives were assessing the frequency and pattern of interventional procedure done in Cath lab of paediatric cardiology department, Bangladesh Shishu Hospital and Institute and their immediate outcome. Methods: It was a cross sectional retrospective study. Total 56 patients of ventricular septal defect (VSD), atrial septal defect (ASD), patent ductus arteriosus (PDA), pulmonary stenosis (PS), aortic stenosis (AS), coarctation of aorta, pulmonary atresia, TGA from January 2019 to December 2019 who underwent trans-catheter interventional procedure by author at Cath lab of paediatric cardiology department, Bangladesh Shishu Hospital and Institute were enrolled in this study. Results: Among 56 patients, PDA device closure done in 19, balloon pulmonary valvuloplasty (BPV) in 13 patients, device closure of ASD in 3 patients, device closure of VSD in 2 patients and balloon aortic valvuloplasty (BAV) in 1 patient. Two patients died; one is pulmonary atresia with PDA dependent pulmonary circulation following ductal stenting another is d-TGA intact IVS with PFO following BAS. One PDA device embolized and retrieved surgically from main and right pulmonary artery. Mean fluoroscopy time=17.29 and mean total procedure time=38.52 min. Conclusions: Trans-catheter interventional procedure for PS, coarctation of aorta, PDA, ASD, VSD, AS, d-TGA, Pulmonary atresia is a safe and some procedure such as BAS for d- TGA, BPV for critical PS, Ductal stenting for pulmonary atresia, Balloon angioplasty for severe coarctation of aorta with LV dysfunction is lifesaving with a low adverse event rate.